A APRENDIZAGEM DE CONTEÚDOS DE FUNÇÕES E ESTATÍSTICA POR MEIO DA MODELAGEM MATEMÁTICA: ALIMENTAÇÃO, QUESTÕES SOBRE OBESIDADE E DESNUTRIÇÃO - Tatsch, Karla Jaqueline Souza (2006)
This dissertation presents a research realized through the process of Mathematical Modeling as strategy of teaching and learning in the first ages of Medium School, discussing the theme Feeding, Questions about Overweight and Malnutrition . It was proposed to verify the methodological possibilities offered by the Mathematical Modeling for the improvement of the learning process of the contents of Mathematical Functions and Statistics. This research was based on research and action and had a qualitative approach, based on questionnaires and lookouts of the activities developed by the pupils. The initial and final questionnaires answered by the students were analyzed and compared, as well as the researsher s lookouts, duly registered in guidelines of comments. The students were able to propose and solve problematic situations based on the proposed theme and assumed an active position on the process of teaching and learning. As a result of the research it could be said that the Mathematical Modeling, as a teaching strategy, made possible the construction of mathematical concepts related with the mathematical functions and statistics and it contributed for the improvement of the learning. The experience of education with Mathematical Modeling enable the students to have the duty of a researcher and to the teacher, indispensable element of the process, the function of a guide.